IMPELEMENTASI PENDIDIKAN KARAKTER DISIPLIN PADA PEMBELAJARAN PPKN KELAS IV SDN PASAR BARU 1 KOTA TANGERANG - Sitti Aisyah Farawansya; Yoyoh Fathurrohmah; Siti Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Sitti Aisyah Farawansya 1986206230 “Implementation of Discipline Character Education in Grade IV Ppkn Learning SDN Pasar Baru 1 Tangerang City”. This study aims to describe: (1) Implementation of disciplinary character education in fourth grade Civics learning at SDN Pasar Baru 1 Tangerang City. (2) Supporting factors and inhibiting factors of disciplinary character education in fourth grade Civics learning at SDN Pasar Baru 1 Tangerang City. This research uses a descriptive qualitative approach. Data collection techniques using interviews, observations, questionnaires and documentation studies. Data analysis in this study used data reduction, data presentation, and conclusion drawing. The results showed that: indicators of obedience to school rules with a percentage value of 62.8% with a sufficient category, obedience to learning activities at school with a percentage value of 67% with a sufficient category, obedience in doing lesson assignments, with a percentage value of 65% with a sufficient category and obedience to learning activities at home with a percentage value of 40.4% with a less category. So the implementation of disciplinary character education in grade IV Civics learning at SDN Pasar Baru 1 Tangerang City is in a good category by having a percentage value of 71.4%. Supporting factors and inhibiting factors, namely from the family environment and instincts (instincts), teachers expect great participation from parents in instilling disciplinary character values, because the role of parents is very important, because the family functions to educate, nurture, and develop students' abilities.